2019
DOI: 10.26565/2220-637x-2019-33-06
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of fullerene C70 in binary organic solvent mixtures as studied using UV-Vis spectra and dynamic light scattering

Abstract: In this paper, the formation of colloidal species of fullerene C 70 in organic solvents was studied. The examining of the UV-visible spectra was accompanied by particle size analysis using dynamic light scattering, DLS. Stock solutions of C 70 in non-polar toluene and n-hexane were diluted with polar solvents acetonitrile and methanol. The appearance of colloidal species with a size within the range of ≈ 50-500 nm is accompanied by alterations of the absorption spectra. In the toluene-acetonitrile and toluene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The decrease in colloidal particle size on approaching pure acetonitrile (Figure ) is in line with Volmer’s known rules: smaller particles appear in the solvent where the solubility of the compound is lower. ,, For much more concentrated fullerene solutions, however, some other regularities are valid …”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The decrease in colloidal particle size on approaching pure acetonitrile (Figure ) is in line with Volmer’s known rules: smaller particles appear in the solvent where the solubility of the compound is lower. ,, For much more concentrated fullerene solutions, however, some other regularities are valid …”
Section: Resultssupporting
confidence: 77%
“…The data are typified in Figure . Our studies on C 70 and C 60 fullerenes demonstrated that the critical composition of the binary solvent, which corresponds to the appearance of colloidal aggregates, depends on the fullerene working concentration. , Therefore, some discrepancies are observed between the results by different authors. ,, In Figure , such a critical composition corresponds to 38 vol % toluene.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The same can be expected for polar ("poor") solvents, where the solvophobic nature of fullerene colloids is undisputable [23,24,[98][99][100][101]. In the recently named systems, it leads to formation of colloidal aggregates owing to solvophobic interactions.…”
Section: Specific Properties Of Molecular Solutions Of Fullerenesmentioning
confidence: 77%